The Identification of Metallophytes in the Fe and Cu enriched Environments of Brookes Point, Palawan and Mankayan, Benguet and their Implications to Phytoremediation - Claveria, Rene; De los Santos, C.; Teodoro, K.; Rellosa, M.; Vallera, N. (Science Diliman: A Journal of Pure and Applied Sciences; Vol 21 No 2 (2009), 2010)
It is important to consider the potential of plants in the remediation or rehabilitation of areas affected by mining as well as their capability of absorbing metals in anomalous amounts which could be an alternative to traditional mining. Phytoremediation is an innovative way of addressing the environmental impacts of mining. Studies on metallophytes have identified some plant species that thrive in nickeliferous laterites and in cupriferous soils. It has been of interest as to how these plants accumulate the heavy metals the soil contains, and specifically how much of the available metals are being taken up by these plants. In Brookes Point, Palawan, some of the identified plants that thrive in nickeliferous laterites, were Sapotaceae planchonella, Apocynaceae alstonia macropylla and Cunoniaceae weinmannia sp. Results showed similar responses among the plant species in terms of the total Fe content in their leaves, stems and roots. The positive relationship between the soil and plant components was observed manifesting the characteristics of indicator plants for Fe. Apocynaceae alstonia macrophylla specifically had high Fe contents in the root system making it also an accumulator and phytostabilizer for Fe. In Mankayan, Benguet, four native fern species that can tolerate the Cu enriched soils were identified and analyzed for Cu using the root-stem-leaf components. These species were Pteridium aquilinum , Dicranopteris linearis , Pteris sp. and Nephrolepis hirsutula . The results showed Nephrolepis hirsutala and Pteris sp. to be the best Cu-tolerant species. These plants were not only considered as indicator plants for Cu manifested by the positive correlation between soil and plant components but also as accumulators and phytostabilizers for Cu due to the high Cu content in their roots. These are characteristics of metallophytes and thus such plants may be used for phytoremediation.
Keywords: Metallophytes, phytoremediation, Brookes Point, Mankayan